Employee Emotions on Employee Performance: The Role of Human Character - Pindo Asti; Dewi Widyaningsih; Agus Priyadi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
This study strives to enhance employee performance by bridging the mediating role of the human character of the Emotional Employee. Employee emotional changes can be boosted by potential human character, which would have the ability to strengthen employee performance. Data has been collected from 227 employees across the profession, and this has been analyzed using structural equation modeling SEM-PLS. The findings of the SEM show that emotional employee have a positive direct effect on the human character. The data results using this quantitative method showed that employees' emotions had a direct positive impact on human character. Emotional wealth has a positive effect on employee performance. The human character holds proven to potentially bridge the inconsistency of employee emotional changes towards optimizing employee performance. From a methodological standpoint, the role of